Agama dan modernisasi: Adaptasi nilai, tantangan kontemporer, dan relevansi di era global - Harsono, Karima Audy Augustine (Maliki Interdisciplinary Journal, 2025)
This article explores the dynamic relationship between religion and modernization in the context of contemporary society. While modernization introduces technological advancement, rationalization, and globalization, often seen as contrary to traditional religious values religion demonstrates a significant ability to adapt and remain relevant. Using a qualitative literature review approach based on three peer-reviewed journals and supported by established theories such as Max Weber’s theory of religious ethics, Emile Durkheim’s theory of social solidarity, and Peter L. Berger’s theory of desecularization, this study finds that religion continues to play a vital role in shaping public ethics and spiritual stability. Religious practices have evolved through reinterpretation of doctrines, integration of digital media, and promotion of inclusive education. The study also reveals challenges such as secularism, consumerism, and moral decline, which further emphasize the necessity of religion as a source of ethical guidance in modern life. Therefore, religion and modernization should not be viewed as oppositional, but as interdependent forces capable of working synergistically to foster a more humane and spiritually grounded society.